On Morphological Analysis of Spatial Deixis in Mǝriaq-mǝriqu Dialect of Sasak Language - Sutarman Sutarman; Martin L. Manda; Hamzah A. Machmoed (Hasanuddin University, 2020)
This paper concentrates on the spatial deixis and its morphological structures in Mǝriaq-mǝriqu dialect of Sasak language. It includes in a typological study with qualitative method. This research employs two forms of data; primary data and secondary data. The primary data include the information obtained from the informants from every dialect. Secondary data are the data obtained from any documents of Sasak language such as folklore. There are two methods of data collection; field linguistic method and library method. Of the two methods, there are two techniques used in collecting data: Observation and interview. The results of this study accommodated all types of demonstratives by Diessel (1999) and Dixon (1988) and discover some new types contributing to the theory. The types of spatial deixis in this dialect are pronominal, adnominal, quantifier, intensifier, identificational, adverbial, verbal, and referential. In term of morphological structure, the demonstrative in this dialect is constructed of some affixes and the combination of two or more spatial deixis. Nominal demonstrative usually becomes stem of other demonstratives. Quantifier is constructed of prefix ‘se-‘plus manner demonstrative adverb(MDA). Intensifier is constructed of prefix ‘s-‘ plus pronominal, LDA is constructed of prefix ‘n-‘ plus pronominal for proximal, MDA is constructed of prefix ‘mer-‘ and ‘m-‘ plus pronominals, verbal demonstrative is constructed of confix ‘pe-q’ plus MDA, Referential demonstrative is constructed of MDA plus suffix ‘-q’.